Associated Factors of Cardiopulmonary Resuscitation Outcomes; a Cohort Study on an Adult In-hospital Cardiac Arrest Registry - Rattananon, Parin; Tienpratarn, Welawat; Yuksen, Chaiyaporn; Aussavanodom, Supassorn; Thiamdao, Natthaphong; Termkijwanich, Phatcha; Phongsawad, Suraphong; Kaninworapan, Parama; Tantasirin, Kanda (Archives of Academic Emergency Medicine, 2024)
Introduction: In-hospital cardiac arrest (IHCA) remains a substantial cause of morbidity and mortality for hospitalized patients worldwide. This study aimed to identify associated factors of return of spontaneous circulation (ROSC) and survival with favorable neurological outcomes of IHCA patients. Method: A two-year retrospective cohort study was conducted at a university-based tertiary care hospital in Bangkok, Thailand, studying adult patients aged ≥ 18 years with IHCA from January 2021 to December 2022. The primary endpoint was sustained ROSC, and the secondary endpoint was survival with favorable neurological outcomes defined as Cerebral Performance Categories (CPC) Scale of 1 or 2 at discharge. Pre-arrest and intra-arrest variables were collected and analyzed using multivariable logistic regression to identify independent factors associated with the outcomes. Results: During the study period, 156 patients were included in the study. 105 (67.3%) patients achieved sustained ROSC after the CPR, 28 patients (18.0%) were discharged alive, and 15 patients (9.6%) survived with a favorable neurological outcome at hospital discharge. Overall, sustained ROSC was higher in patients who had IHCA during the day shift (odds ratio (OR): 4.11; 95% confidence interval (CI): 1.05-16.06) and electrocardiogram (ECG) monitoring prior to arrest (OR: 6.38; 95% CI: 1.18-34.54). In contrast, higher adrenaline doses administrated, and increased CPR duration reduced the odds of sustained ROSC (OR: 0.72; 95% CI: 0.54-0.94 and OR: 0.92; 95% CI: 0.85-0.98, respectively). Arrest due to cardiac etiology was associated with increased discharged survival with favorable neurological outcomes (OR: 13.43; 95% CI: 2.00-89.80), while a higher Good Outcome Following Attempted Resuscitation (GO-FAR) score reduced the odds of the secondary outcome (OR: 0.89; 95% CI: 0.81-0.98). Conclusion: The sustained ROSC was higher in IHCA during the daytime shift and under prior ECG monitoring. The administration of higher doses of adrenaline and prolonged CPR durations decreased the likelihood of achieving sustained ROSC. Furthermore, patients with cardiac-related causes of cardiac arrest exhibited a higher rate of survival to hospital discharge with favorable neurological outcomes.